2022
DOI: 10.3389/fpsyg.2022.1055505
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CSR on green purchase intention: Empirical evidence from the green building Industries in Taiwan

Abstract: IntroductionWorldwide supplies are being utilized at a disturbing rate and to a significant degree, the building business has been accountable for this ecological deprivation, particularly because of its elevated level of energy expenditure. Hence, this research paper targets the customers of green building industries in Taiwan and developed a framework based on Carroll’s corporate social responsibility (CSR) model, theory of planned behavior (TPB), and cognitive consistency theory (CCT), to measure the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 124 publications
(199 reference statements)
1
7
0
Order By: Relevance
“…This study demonstrated that QS positively impacted young runners' intention to use wearable devices (β=0.163; t=2.170; p<0.05). Furthermore, PE (β=0.214; t=3.167; p<0.01) and PU (β=0.494; t=8.221; p<0.001) had significant positive effects on QS, aligning with previous research [14]. Previous studies have indicated that linking the quantified self with data helps users contextualize events and that combining quantitative data and qualitative experiences strengthens long-term usage habits [75,76].…”
Section: Comparison With Other Studiessupporting
confidence: 84%
See 1 more Smart Citation
“…This study demonstrated that QS positively impacted young runners' intention to use wearable devices (β=0.163; t=2.170; p<0.05). Furthermore, PE (β=0.214; t=3.167; p<0.01) and PU (β=0.494; t=8.221; p<0.001) had significant positive effects on QS, aligning with previous research [14]. Previous studies have indicated that linking the quantified self with data helps users contextualize events and that combining quantitative data and qualitative experiences strengthens long-term usage habits [75,76].…”
Section: Comparison With Other Studiessupporting
confidence: 84%
“…Furthermore, in addition to the CI of users [14], several theories exist for analyzing consumers' attitudes (ATT) toward the current digitalization of products. However, the technology acceptance model (TAM) is considered to be the most relevant and popular theory for measuring 'consumers' ATT toward a product [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers expect green companies to be ethical and credible in meeting environmental commitments (Xu et al, 2022). Therefore, whichever green company shows higher credibility gains higher trust among consumers and subsequently positively affects the green purchase intention of those consumers (Tao et al, 2022). Conversely, waning trust lowers green purchase intent (Rom an-Augusto et al, 2022).…”
Section: Green Purchase Intentionmentioning
confidence: 99%
“…Scholars have examined the influence of cognitive factors (Ahmad and Zhang, 2020; Issock et al , 2020) and affective factors (Chen, 2010; Ha, 2022; Hameed et al , 2019; Wei et al , 2017) on green trust. Additionally, in the realm of green business, consumer responses matter most – such as positive word-of-mouth (Ahmad and Zhang, 2020; Guerreiro and Pacheco, 2021; Issock et al , 2020), loyalty (Baktash and Talib, 2019), green brand equity (Chen, 2010; Ha, 2022), green purchase intention (Tao et al , 2022; Xu et al , 2022) and actual buying behavior (Sh. Ahmad et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Customers' intentions to buy and use a product longer are significantly impacted by positive WoM (Ruangkanjanases et al, 2020). Customers frequently prefer the goods and services their loved ones like, taking into account both the emotional pull of the product and the brand's reputation (Tao et al, 2022). Promotion in the travel sector is primarily reliant on WoM.…”
Section: 43mentioning
confidence: 99%